Voltage-Dependent Anion Selective Channel 3: Unraveling Structural and Functional Features of the Least Known Porin Isoform - Reina, Simona; Checchetto, Vanessa (Frontiers in Physiology, 2022)
VDAC are pore-forming proteins located in the outer mitochondrial membrane. Three isoforms are coded by separate genes in mammals (VDAC1-3). These proteins have a crucial role in the cell, forming the primary interface between the mitochondrial and cellular metabolisms. Research on the VDACs role in the cell is a rapidly growing field, but VDAC3 function remains elusive. The high-sequence similarity between isoforms is suggestive of a similar pore-forming structure. Electrophysiological analyses revealed that VDAC3 works as a channel; however, its gating and regulation remain debated. A comparison between VDAC3 and VDAC1-2 underlines the presence of a higher number of cysteines in both isoforms 2 and 3. Recent mass spectrometry data demonstrated that the redox state of VDAC3 cysteines is evolutionarily conserved. Accordingly, these residues were always detected as totally reduced or partially oxidized, thus susceptible to disulphide exchange. The deletion of selected cysteines significantly influences channel function. Some cysteine mutants of VDAC3 exhibited distinct kinetic behaviour, conductance values and voltage-dependence, suggesting that channel activity can be modulated by cysteines’ reduction/oxidation. These properties point to VDAC3 as a possible marker of redox signaling in the mitochondrial intermembrane space. Here we summarize our current knowledge about VDAC3 predicted structure, physiological role and regulation, and possible future directions in this research field.